An ultra scale‐down method to investigate monoclonal antibody processing during tangential flow filtration using ultrafiltration membranes. Issue 3 (4th January 2019) - Fernandez‐Cerezo, Lara; Rayat, Andrea C. M. E.; Chatel, Alex; Pollard, Jennifer M.; Lye, Gary J.; Hoare, Michael
Abstract: The availability of material for experimental studies is a key constraint in the development of full‐scale bioprocesses. This is especially true for the later stages in a bioprocess sequence such as purification and formulation, where the product is at a relatively high concentration and traditional scale‐down models can require significant volumes. Using a combination of critical flow regime analysis, bioprocess modelling, and experimentation, ultra scale‐down (USD) methods can yield bioprocess information using only millilitre quantities before embarking on highly demanding full‐scale studies. In this study the performance of a pilot‐scale tangential flow filtration (TFF) system based on a membrane flat‐sheet cassette using pumped flow was predicted by devising an USD device comprising a stirred cell using a rotating disc. The USD device operates with just 2.1 cm 2 of membrane area and, for example, just 1.7 mL of feed for diafiltration studies. The novel features of the design involve optimisation of the disc location and the membrane configuration to yield an approximately uniform shear rate. This is characterised using computational fluid dynamics for a defined layer above the membrane surface. A pilot‐scale TFF device operating at 500‐fold larger feed volume and membrane area was characterised in terms of the shear rate derived from flow rate‐pressure drop relationships for the cassette. Good agreement was achieved between the USD and TFF devices for the flux and resistance values at equivalent average shear rates for a monoclonal antibody diafiltration stage. Abstract : This paper describes the creation of an ultra scale‐down sheared‐membrane device using a new rotating‐disc design and membrane geometry to go from varied shear rates over the membrane surface (A) to more uniform better‐defined shear rate (B). Only 2.1 cm2 of membrane area is used allowing processing tests of just 1.7 mL of material under defined shear and independently‐varied transmembrane pressure drop. Collaboration with Merck & Co. has allowed verification of USD predictions at pilot scale using 0.11 m2 membrane cartridges.